The elite athlete - assessing body shape, size, proportion and composition - Kerr, D. A.; Ackland, T. R.; Schreiner, A. B. (Asia Pacific Journal of Clinical Nutrition)
In the quest to optimize performance of the elite athlete the sport scientist has sought to determine the ideal physique for a given sport or event. For some sports, specific structural characteristics offer definite performance advantages; for example in rowing, in addition to height, a large arm span has been identified as important. In other sports. such as long distance running, low levels of adiposity or 'fatness' appear to be linked with faster running times. There are four areas where appraisal of the athlete's physique can provide useful information: (1) identification of talented athletes; (2) to assess and monitor the growing athlete; (3) to monitor training and performance; and (4) to determine 'race weight' in weight-category sports. As a research tool a particular method must be reliable and valid. Other considerations include how expensive the method is, if it is suitable for a field situation and if large amounts of data on a number of subjects can be collected quickly. The method should be safe for both the athlete and the tester and provide useful feedback for the athlete or coach. Anthropometry, with training is able to fulfil most of these criteria and is the most widely used method of physique assessment in sports science. Large anthropometric data bases have been collected on elite athletes at Olympic games and world championships according to a standard protocol. Kinanthropometry, which has developed from anthropometry, is concerned with measurement and evaluation of different aspects of human movement and individual variation in body shape, size, proportion and composition. For the assessment of adiposity a sum of skinfolds, usually over six sites, is most commonly used rather than percentage body fat formulae. Muscle mass can be assessed indirectly through girth and corrected girth measurements. Limb lengths and breadths are used to assess skeletal structure and proportional differences in limb size. The anthropometric methods most commonly used to describe the physique of the athlete, which appraise shape, size, proportion and composition, will be discussed.